Self-Access Language Learning Programme: The Case of the English Language Voluntary Intensive Independent Catch-up Study - Papadima-Sophocleous, Salomi (My University, 2013)
This study investigated whether and to what extent an English Language Voluntary Intensive Independent Catch-up Study (ELVIICS), a Self-Access Language Learning (SALL) programme, was effective in helping first-year Greek-Cypriot students fill in the gaps in their English language learning and come closer to the required language competence level of the Common European Framework of Reference (CEFR) B1 level. It also examined students’ perceptions of such learning. The students followed the ELVIICS at their own pace, time and space until they felt they had reached the aimed level. Analysis of the achievement test results revealed that students’ language competence improved and reached the required level. Additional quantitative data also revealed that students felt ELVIICS also helped them improve their self-confidence, computer skills and autonomous learning. Moreover, students claimed that ELVIICS assisted them in getting through and successfully completing their compulsory course.
Keywords: SALL; SAC; ESL; Cypriot university